Sensory sweetness and sourness interactive response of sucrose-citric acid mixture based on synergy and antagonism - Yuezhong Mao; Shiyi Tian; Yumei Qin; Shiwen Chen (npj Science of Food, 2022)
Abstract The clarity of taste sensation interaction is a key basis for promoting the food sensory science research and its application to the beverage and food additive industries. This study explored the synergy and antagonism effect of sucrose-citric acid mixture and established an optimized method to determine the human sweetness and sourness interactive response. Sucrose-citric acid mixtures were evaluated by the “close type” question. According to the sensory difference strength curves and Weber–Fechner law, citric acid increased the sucrose’s absolute threshold (0.424–0.624%) and weber fraction (20.5–33.0%). Meanwhile, sucrose increased citric acid’s absolute threshold (0.0057–0.0082%) and decreased its weber fraction (17.96–9.53%). By fitting absolute threshold and weber fraction variation equations, the sweet–sour taste sensory strength variation models (SSTVM) were derived, which could be used to explain the synergy and antagonism effect of sweet–sour taste. According to the SSTVM, the interactive response to sweet–sour taste could be quantitatively calculated. The high coincidence between SSTVM and human evaluation (1.02% of relative error) indicated that it could be applied in the food industry, health management, and intelligent sensory science.